Valgete Akaatsiate Varjus - Chepelyk, Oksana (Ukraine, 2013)
The film explores life in a Ukrainian village focusing on a family mourning after the death of their eldest son. Pre-Maidan (revolution) rural landscape in the Ukraine.
Verzio Film Festival Submission
Duration: 01:15:00
Verzio Film Festival Submission
Keywords: Documentary films